1988
DOI: 10.1152/jappl.1988.64.2.543
|View full text |Cite
|
Sign up to set email alerts
|

Genioglossus and breathing responses to airway occlusion: effect of sleep and route of occlusion

Abstract: We examined the effect of sleep state on the response of genioglossus muscle (EMGgg) activity to total airway occlusion applied at 1) nasal (N) airway [and thus exposing the upper airway (UAW) to pressure changes] and 2) tracheal (T) airway (thus excluding UAW from pressure changes). A total of 233 tests were performed during wakefulness (W), 98 tests in slow-wave sleep (SWS), and 72 tests in rapid-eye-movement (REM) sleep. Prolongation of inspiratory time (TI) of the first occluded effort occurred in all test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
4

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 0 publications
6
31
4
Order By: Relevance
“…Alternatively, the response to increases in flow may result from changes in airway pressure likely to result from shortening of tI for a constant delivered VT. Pressure receptors are also known to exist in the larynx and their response to negative pressure has been studied. Contrary to our observations, sleep reduces the laryngeal response to application of negative pressure in the airway [23]. Positive pressure is known to be a less intense stimulus than negative pressure [24].…”
Section: Discussioncontrasting
confidence: 99%
“…Alternatively, the response to increases in flow may result from changes in airway pressure likely to result from shortening of tI for a constant delivered VT. Pressure receptors are also known to exist in the larynx and their response to negative pressure has been studied. Contrary to our observations, sleep reduces the laryngeal response to application of negative pressure in the airway [23]. Positive pressure is known to be a less intense stimulus than negative pressure [24].…”
Section: Discussioncontrasting
confidence: 99%
“…However, these changes allowed larger tidal volumes to be generated during nasal breathing. These results are similar to those reported in the awake and sleeping dogs during externally applied nasal occlusion tests (Issa et al 1988), and suggest that the change in breathing pattern during nasal breathing serves to protect the upper airway from narrowing, particularly during sleep. Several respiratory stimuli induce arousal, including hypoxia (Bowes et al 1981;Berthon-Jones & Sullivan, 1982;Hedemark & Kronenberg, 1982), hypercapnia (Berthon-Jones & Sullivan, 1984), negative intrathoracic pressure (Gleeson et al 1990), upper airway mechanoreceptors (Issa & Sullivan, 1983;Issa et al 1987), and stimuli from thoracic pump muscles (Vincken et al 1987).…”
Section: Discussionsupporting
confidence: 88%
“…The results of these studies indicated that breathing through the nares is different from that during tracheal breathing. The dissimilarity was not due to differences in dead space or airway resistance since both these variables were matched (McNamara et al 1986;Issa et al 1988;Plowman et al 1990). The present study confirms these findings and extends the results to both NREM and REM sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients have OSA only during REM sleep (123). Although human physiological data are challenging to obtain and the available literature is relatively scarce, REM sleep is associated with decreased upper airway muscle tone (124,125), impaired genioglossus reflex responsiveness to negative pressure (26,126,127), and reduced chemosensitivity (128,129). These factors may worsen apnea during REM sleep.…”
Section: Rem Sleepmentioning
confidence: 99%